(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Esophageal varices rupture is a serious complication of cirrhosis-related portal hypertension, which carries a high mortality rate of approximately 40%. In Vietnam, there has been an increase in bleeding cases due to esophageal varices in emergency rooms. Objective: The objective of this research is to examine the pathological characteristics of patients with cirrhosis and esophageal varices rupture at Thai Binh Provincial General Hospital. Methods: A cross-sectional descriptive study was conducted on 110 patients treated at the Department of Internal Gastroenterology from May 2021 to August 2022. Variables such as age, gender, medical history, clinical symptoms, subclinical symptoms, combined lesions, and degree of cirrhosis were recorded. Results: The results showed that 94.5% of patients were male, with an average age of 55.3 ± 9.3 years old. The most common age group was 50-59, accounting for 48.2%. 79.1% had a history of alcoholism and 14.5% had hepatitis B and C virus infections. The rates of moderate and severe gastrointestinal bleeding were 46.4% and 29.5%, respectively. Over 70% of patients exhibited symptoms such as vomiting blood, black stools, ascites, and collateral circulation. All patients (100%) had anemia (50.9% severe anemia), 83.6% had thrombocytopenia, and 75.5% had decreased prothrombin. The study also found that 95.5% of patients had decreased albumin, 75.5% had increased levels of glutamic oxaloacetic transaminase (GOT), and 64.5% had increased levels of glutamic pyruvic transaminase (GPT). Additionally, 41.8% had increased blood urea, 81.8% had increased total bilirubin, and 10.9% had liver atrophy on ultrasound. Furthermore, 63.6% had grade 3 esophageal varices, and the rate of Child-Pugh B and C cirrhosis was 59.1% and 40.9%. Conclusion: The study concluded that patients with esophageal varices rupture due to cirrhosis who seek treatment at Thai Binh Provincial General Hospital are often in an advanced stage with significant liver function decline. 40.9% of the patients had Child-Pugh C cirrhosis, 63.6% had grade 3 esophageal varices with 4-5 varicose veins, and the ratio of GOT/GPT was greater than 1.